Stratigrafi gunung api daerah Bandung Selatan, Jawa Barat - Bronto, Sutikno; Koswara, Achnan; Lumbanbatu, Kaspar (Indonesian Journal on Geoscience, 2006)
http://dx.doi.org/10.17014/ijog.vol1no2.20064The aim of this volcano stratigraphic study is to understand the historic relationship of each volcanoes in the South Bandung area. Methods used in this study are landsat analyses, fi eldwork, petrographic studies, and radiometric dating. Physiographically, South Bandung is composed of mountaineous area, hilly area, and high plain of Pangalengan and Bandung itself. Based on volcanic stratigraphy, volcanic rocks there are divided into eleven rock units, nine of them are identifi ed their volcanic sources, having Pliocene to Quaternary ages. The presence of subsurface Miocene volcanic rocks supports the super imposed volcanisms from Tertiary to Quaternary in this area. Mineral resources of sulphide metals are found in the central facies of Soreang, Kuda, and Dogdog volcanoes. Whereas, geologic hazards covering tectonic earthquakes, volcanic eruptions, and landslides also threaten this area. Mineral explorations and hazard mitigations are necessary to the presence of mineral resources and geologic hazard potential. Â